Regulating the Systemic Risk - Tiainen, Panu (My University, 2013)
Financial systems tend to experience intermittent crises. Globalization, integrated financial markets and complicated financial products have revolutionized the financial system. These drastic changes contributed to the inception of a financial crisis in 2007. The crisis quickly spread to the real economy all over the world. The financial crisis of 2007–2008 can be considered as the first global financial crisis. The concept of systemic risk refers to the collapse of an entire market or financial system. The systemic risk has gained increasing attention in the aftermath of the financial crisis of 2007–2008. The systemic risk derives from banks’ exposure to common risks or contagion effects of financial institutions. Realization of the systemic risk causes considerable damages to the entire financial system. The financial crisis led to the reform of risk measuring methods. Risk measuring methods have an essential role in the regulation of the systemic risk. This thesis discusses the VaR, CoVaR and SES methods. The VaR method is a common tool used to measure market risk. However, VaR merely measures the risk of individual institutions. Therefore, this thesis presents the CoVaR and SES methods as tools to measure the systemic risk. The CoVaR method is based on the VaR- method, but the effect of an individual institution in the entire system’s risk can be estimated by using CoVaR. The goal of macroprudential supervision is to identify and prevent the systemic risks and vulnerabilities which threaten the stability of the financial system. This thesis examines the role of regulation and supervision in limiting the systemic risk and securing banks’ capital adequacy. The Basel III regulations are expected to play a significant role in the regulation of systemic risk. However, as regulation has its costs, this thesis also examines the possible effects of the regulation.
Keywords: Systemic risk; financial crisis; regulation; Basel III; effects of regulation.; fi=Taloustiede|en=Economics|; fi=Taloustieteen maisteriohjelma|en=Master's Programme in Economics|